Mengukur Tingkat Kesesuaian antara Standar Akuntansi Keuangan dengan International Financial Reporting Standards per 1 Januari 2008 - Panggabean, Rosinta Ria (Binus Business Review, 2010)
International accounting topic was rare to adress between accounting practices, especially International Accounting Standard. It occured due to the restrictive source and difficulty in finding the source. However, recently the standard has been an addressed issue since Indonesia Chartered of Accountant (IAI) plans to comply the Indonesia Accounting Standard (SAK) with the International Financialreporting(IFRS)on1stJanuary2012.The purpose of the research is to measure the compliance of the (SAK) per 1st January 2008 with the IFRS per 1st January 2008 and attain the association between those two standards. Hence, the difference between the two standards and the neccessary steps to be taken for complying can be obtained. The methodology will be used in the paper are Jaccardâs Coefficients, Spearmanâs Correlation Coefficient,Euclidean Distances.The sample for the paper will be 43 accounting issues adressed on both standards that have been chosen and investigated. The paper concludes that there are significant equalities (75%) between SAK per 1st January 2008 and IFRS 1st January 2008. (using Jaccardâs Coefficients). Due to several problems that have been found in the research, the author wish that the further researchers could widen the researchâs samples, so the result will be more accurate and comprehensive.Â